Transient receptor potential vanilloid 1 (TRPV1) antagonism in patients with refractory chronic cough: A double-blind randomized controlled trial - Khalid, Saifudin; Murdoch, Robert; Newlands, Amy; Smart, Kevin; Kelsall, Angela; Holt, Kimberley; Dockry, Rachel; Woodcock, Ashley; Smith, Jaclyn A. (Journal of allergy and clinical immunology, 2014)
Inhalation of capsaicin, the extract of hot chili peppers, induces coughing in both animals and human subjects through activation of transient receptor potential vanilloid 1 (TRPV1) on airway sensory nerves. Therefore the TRPV1 receptor is an attractive target for the development of antitussive agents. We sought to assess the antitussive effect of TRPV1 antagonism in patients with refractory chronic cough. Twenty-one subjects with refractory chronic cough (>8 weeks) attending a specialist clinic were recruited to a randomized, double-blind, placebo-controlled crossover trial assessing a TRPV1 antagonist (SB-705498). Cough reflex sensitivity to capsaicin (concentration of capsaicin inducing at least 5 coughs) and 24-hour cough frequency were coprimary end points assessed after a single dose of SB-705498 (600 mg) and matched placebo. Cough severity and urge to cough were reported on visual analog scales, and cough-specific quality of life data were also collected. Treatment with SB-705498 produced a significant improvement in cough reflex sensitivity to capsaicin at 2 hours and a borderline significant improvement at 24 hours compared with placebo (adjusted mean difference of +1.3 doubling doses at 2 hours [95% CI, +0.3 to +2.2; P = .0049] and +0.7 doubling doses at 24 hours [95% CI, +0.0 to +1.5; P = .0259]). However, 24-hour objective cough frequency was not improved compared with placebo. Patient-reported cough severity, urge to cough, and cough-specific quality of life similarly suggested no effect of SB-705498. This study raises important questions about both the role of TRVP1-mediated mechanisms in patients with refractory chronic cough and also the predictive value of capsaicin challenge testing in the assessment of novel antitussive agents.